1990
DOI: 10.1159/000185984
|View full text |Cite
|
Sign up to set email alerts
|

Lupus Nephritis with Adult T Cell Leukemia

Abstract: A 64-year-old Japanese male patient with lupus nephritis associated with adult T cell leukemia (ATL) is described. Percutaneous renal biopsy demonstrated findings consistent with membranous lupus nephritis. To our knowledge, this is the first case of lupus nephritis complicated by ATL, suggesting that human T cell leukemia virus type I may be correlated not only to outbreaks of ATL but also to lupus nephritis/systemic lupus erythematosus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Both in humans [12][13][14]18] and in mice [15,16], the results of previous research have suggested the involvement of C-type retroviruses, including HTLV-1, in the pathogenesis of SLE. While SLE with ATL or HAM is rare in the clinical setting, several reports have described these comorbidities [19][20][21][22]26]. Compared with the previous cases, the most pathognomonic features of this patient are that his renal pathology showed lupus nephritis and marked T-lymphocyte infiltration into the interstitium (Figs.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Both in humans [12][13][14]18] and in mice [15,16], the results of previous research have suggested the involvement of C-type retroviruses, including HTLV-1, in the pathogenesis of SLE. While SLE with ATL or HAM is rare in the clinical setting, several reports have described these comorbidities [19][20][21][22]26]. Compared with the previous cases, the most pathognomonic features of this patient are that his renal pathology showed lupus nephritis and marked T-lymphocyte infiltration into the interstitium (Figs.…”
Section: Discussionmentioning
confidence: 64%
“…The mechanism underlying how HTLV-1 causes SLE remains elusive, but the postulated roles for such retroviruses in the etiopathogenesis of SLE are considered to include intrinsic effects, mimicry of antigens, and/or effects as stimulators of autoimmunity [17,18]. In fact, there have been previous case reports of patients with SLE and ATL [19,20], SLE and HAM [21,22], and SLE and the persistent carrier state of HTLV-1 infection [23]. We herein report the first case in which a kidney biopsy revealed lupus nephritis with interstitial nephritis that might partly include oncogenic T lymphocytes in an HTLV-1 positive patient.…”
Section: Introductionmentioning
confidence: 99%
“…The association between HTLV-1 and scleroderma is also rare [16]. Although some investigators have described an association between HTLV-1 and SLE [17][18][19][20], others have described a negative association between HTLV-1 and SLE [21,22]. Therefore, the precise association between HTLV-1 and various autoimmune diseases has not been fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…HTLV-1is the first detected exogenous human type C retrovirus that was isolated from patients with ATL(5, 6), and has been found to have a close relation to outbreak not only of leukemia or lymphomabut also of HAM/TSP.Someinvestigators have studied the etiological role of HTLV-1for SLE, but they have found no evidence for the participation of HTLV-1 infection in human SLE (16,17). On the other hand, Scott et al reported SLE with thrombocytopenia infected with HTLV-1 (18) and Ito et al reported case of lupus nephritis with ATL, and suggested that HTLV-1infection might be linked to SLE (19).…”
Section: Discussionmentioning
confidence: 99%